2020
DOI: 10.1002/chem.201905785
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the Controlled Covalent Double Functionalization of Graphene Oxide

Abstract: Graphene oxide (GO) is av ersatile platform with unique properties that have found broad applications in the biomedical field. Double functionalization is ak ey aspecti n the designo fmultifunctional GO with combined imaging, targeting, and therapeutic properties. Compared to noncovalent functionalization, covalents trategies lead to GO conjugates with ah igher stability in biological fluids. However, only af ew double covalentf unctionalization approaches have been developed so far.T he complexity of GO makes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 39 publications
(49 reference statements)
1
19
0
Order By: Relevance
“…[24][25][26][27] Compared to noncovalent complexation, covalent functionalization enables us to prepare more stable conjugates and minimize the release of molecules adsorbed onto the GO surface, especially for biological applications. Several strategies have been reported to functionalize GO covalently by targeting different functional groups such as carboxylic acids, 28 epoxide rings 29 and hydroxyl groups [30][31][32][33] allowing the development of approaches for double functionalization. 31,32,34 However, the derivatization of the carboxylic acids leads to very low loading efficiency compared to the functionalization of the hydroxyl and epoxide moieties, due to the limited amount of COOH on GO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][27] Compared to noncovalent complexation, covalent functionalization enables us to prepare more stable conjugates and minimize the release of molecules adsorbed onto the GO surface, especially for biological applications. Several strategies have been reported to functionalize GO covalently by targeting different functional groups such as carboxylic acids, 28 epoxide rings 29 and hydroxyl groups [30][31][32][33] allowing the development of approaches for double functionalization. 31,32,34 However, the derivatization of the carboxylic acids leads to very low loading efficiency compared to the functionalization of the hydroxyl and epoxide moieties, due to the limited amount of COOH on GO.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies have been reported to functionalize GO covalently by targeting different functional groups such as carboxylic acids, 28 epoxide rings 29 and hydroxyl groups [30][31][32][33] allowing the development of approaches for double functionalization. 31,32,34 However, the derivatization of the carboxylic acids leads to very low loading efficiency compared to the functionalization of the hydroxyl and epoxide moieties, due to the limited amount of COOH on GO. 29 Therefore, a higher amount of carboxylic acids would broaden the possibilities for multi-functionalization of GO with a high loading efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…All biological experiments were performed using the same batch of material. 55 According to XPS, RCND-DTPA- gram of RCND-DTPA-Gd, we found that there is one Gd atom every 90 C atoms (52.9/0.586).…”
Section: Preparation Of Rcnd-dtpa-gdmentioning
confidence: 89%
“…Due to the characteristics of GO, it is often regarded as an effective platform for obtaining functionalized or modified graphene based materials. [ 7‐10 ]…”
Section: Background and Originality Contentmentioning
confidence: 99%